(3GdJYQja HBd HjJ GdfHi Udi Gddg Ydjg hSdes - (3CHh RjO Hf YHO GdQMef GdbjQhGfjs
(3ChdgG (B:s
(3GdMeO ddg GdPi cQe Hfi BOe haVdge Ydi cKjQ eef Ndb JaVjdkG bGd CHh RjO Hf YHO GdQMef GdbjQhGfi deG QCjJ MH Bd HjJ GdfHi GdcQjeef C(B'(3Xe GdhSGFd hEcQGege YfO Gddg MQcfi HGYK GdMH Cf CLeY dge JCdjakG HGdJYQja s
(3BNQgG (B:s
(3BNQ GdehLhO efgG HYfhGf (B: (3PcQ TQaGA Hfi djK , bhdg (B: (3hHfi NQja hHfi LQehf , hai GdRGhjI hai fGMjI SHJI , hge ef CMaGO GdTjN CHj GdaVd CMeO Hf YHO GdhGMO Hf YHO GdcQje Hf eMeO Hf ehdGfG YHO GdSdGe Hf efjS GdMSfi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI (B_ (3GdQHGW (B(1499 (3O(B) s
Keywords: (3GdJGQjNs